Learning Model for Autistic and Dyslexic Children - Rachit Mehul Pathak; Ajay Varma Mudunuri; Varun Patrikar (Innovative Research Thoughts, 2023)
The purpose of the project is to create a learning software for autistic and dyslexic children. The goal of the project is to make the children choose a language and then using a custom speech -to- text classifier make the children repeat and pictographically learn various words. Teaching autistic and dyslexic is a very difficult task as they have a difficulty in learning and differentiating between different languages. We aim to create the model and categorize words from different languages, mainly English and Hindi. Currently, with models present, the problem in the models is that they are unable to detect the accent in which native Indian speakers speak. Thus, creating a model which can be used naturally over the whole country is a difficult task. The created model would be able to differentiate and understand a handful of words, and with a much powerful engine and dataset, it would be able to act as a modern-day text to speech and a teaching tool for the autistic and dyslexic children.